The Effectiveness of Student MSME Management in Increasing Business Profits in Gorontalo City - Nabila D. Pakaya; Tri Handayani Amaliah; Ikhlas Ul Aqmal (Economics and Digital Business Review, 2026)
This study aims to determine the effectiveness of student MSME management in increasing business profits in Gorontalo City. The data analysis used in this study is a descriptive qualitative approach using primary and secondary data sources. The data collection method was carried out through observation, interviews, and documentation. Based on the results of the study, it shows that the effectiveness of student MSME management in increasing business profits is seen from several aspects, namely financial management, information management, operational management, and business control and supervision have been running quite well, but not fully optimal. Some student MSME actors still use simple business management, especially in financial recording and business control. The operating profit obtained has increased, but it is still fluctuating because it is influenced by sales levels, the number of consumers, operational costs, raw material prices, and market conditions. Therefore, more effective and structured business management is needed so that the increase in business profits can be more stable and sustainable.